ANALISIS PENGARUH KEBIJAKAN MONETER TERHADAP INFLASI DAN PEREKONOMIAN DI INDONESIA - Amrini, yassirli; Aimon, Hasdi; Syofyan, Efrizal (Jurnal Kajian Ekonomi, 2014)
This article focused on analyze (1) Effect of the money supply, money supply of previous period, Â the SBI (Central Bank Sertificate) rate, exchange rate, and economy to inflation in Indonesia (2) The influence of inflation, domestic investment, domestic investment of previous period, foreign invesment, foreign invesment of previous period, and labor to economy in Indonesia. Data used time series of (I year kuartal 2000 â€“ IV year kuartal 2011). This article use analyzer model equation of simultaneous with method of Two Stage Least Squared (TSLS) The result of research concludes that (1) the money supply have a significant and positive impact on the inflation, the money supply of previous period have a significant and positive impact on the inflation, the SBI rate have significant and negative impact on the inflation, the exchange rate have significant and positive impact on the inflation. While the economy is not significant and positive impact on the inflation. If the money supply increase, the inflation will appreciate. If the money supply of previous period increase, the inflation will also appreciate. If the the SBI rate increase, the inflation will depreciate. If the exchange rate increase, the inflation will appreciate. If the economy increase, the inflation will appreciate. (2) The domestic investment, domestic investment of previous period, foreign invesment, foreign invesment of previous period, and labor significantly influence the economy in Indonesia, while the inflation is not significant on the economy in Indonesia. Keywords : Money supply, the SBI (Central Bank Sertificate) rate, exchange rate, economy,, inflation, domestic investment, foreign invesment, and labor